299. Geographic mediation of dose for PIERs On the Move (POM) in the Community Level Intervention for Preeclmpsia (CLIP) in Mozambique - Makanga, Prestige Tatenda; Dube, Yolisa; Sharma, Sumedha; Bone, Jeffrey; Saccor, Charfudin; Makacha, Liberty; Payne, Beth; Macuacu, Salesio; Vidler, Marianne; Vala, Anifa; Magee, Laura; Lee, Tang; et al. (Elsevier, 2022)
Travel time and distance to health facilities are known barriers for accessing maternal health care, particularly in Mozambique. Community health workers (CHWs) are responsible for extending the reach of antenatal care to isolated communities. Less is known about the geographical barriers faced by CHWs that may hamper their access to these isolated communities. Objective